The Effect of Dividend Policy, Debt Policy, and Profitability on Company Value in LQ45 Index - Asia, Crysanti Chandra; Wikartika, Ira (Jurnal Ilmu Manajemen Advantage, 2024)
The company value as indicated by the stock price is one of the things that investors take into consideration. This study has a purpose to find out about how dividend policy, debt policy, and profitability affect on company value. This study’s object is the LQ45 index companies on the Indonesia Stock Exchange during 2020-2023 period. Purposive sampling method was used in this study and obtained 22 companies in the four years observation period so there is 88 observation data were obtained. The technique of analysis that used is multiple linear regression analysis by SPSS version 25. This study’s results is indicate that there is no effect in Dividend Policy (DPR) on Company Value (PBV). While Debt Policy (DER) and Profitability (ROA) are significantly positive on Company Value (PBV).